Influence of the processing conditions and corona poling on the morphology of β-PVDF - Sencadas, V.; Lanceros-Mendéz, S.; Gregorio Filho, R.; Chinaglia, D. L. [UNESP]; Pouzada, A. S. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
The α → β phase transformation of PVDF through the stretching process at different temperatures was investigated. The optimum stretching conditions were studied and characterised by infrared spectroscopy and differential scanning calorimetry. The maximum β-phase content was achieved at 80°C and a stretch ratio of 5. These samples were poled at several electric fields by the corona charge method. The effect of the electric field on the phase transformation was studied by infrared spectroscopy.
Keywords: Differential scanning calorimetry; Electric corona; Electric field effects; Infrared spectroscopy; Phase transitions; Corona charge methods; Phase content; Stretch ratio; Stretching process; Polymers